From Vandhyatva to Garbhadhana - A Multimodal Ayurvedic Approach to Secondary Infertility - Yogita Kumari,; Diksha Khathuria,; Anu M.S,; Narendra Kumar Meena, (AYUSHDHARA, 2025)
Secondary infertility is defined as the inability to conceive after one previous conception. Multiple factors like Ovulatory dysfunctions 30-40%, tubal disease 20-35%, uterine factor 10%, cervical factors 5% and pelvic endometritis 1-10% contribute in infertility cases. This case report discusses a 28-year-old woman who presented with secondary infertility following a miscarriage. Chief complaints of irregular menstrual cycles characterised by delayed and scanty menses (oligomenorrhea), weight gain, and mild hirsutism. An ultrasound confirmed polycystic ovarian syndrome (PCOS). Diagnostic evaluations, including hysteroscopy, revealed endometritis, bilateral tubal thickening at the cornual site, and signs of PID. She had a previous laparoscopy with ovarian drilling and cannulation. Initial treatment started with Deepana-Pachana medicines (digestive and detoxifying agents) and was followed by Shatapushpa Churna and Tila Shelu Karvi Kwath along with Pushpadhanva Rasa. After regulating her menstrual cycle, Phalaghrita and Matra Basti (medicated enema) with Hingutriguna Taila were added to the regime. By effectively addressing the facilitating conception, along with regulating her menstrual cycle, this treatment approach eased her to carry a healthy intrauterine pregnancy.